UNSUR RUPA DAN MAKNA PADA BUSANA PENGANTIN BETAWI - Ayoeningsih Dyah Woelandhary (Jurnal Budaya Nusantara, 2019)
Bridal dress is found in all cultures in the archipelago, its existence is often used as a focal pointfor invited guests, so it is not surprising that fashion is one of the elements that most brides payattention to. Variety of designs and modifications are made by designers and brides to wear,but ingeneral the basic form is not removed, it is manifested in maintaining the spirit of culturalvalues embedded in it. The focus of this research is the Betawi regional wedding dress. ThisBetawi tribe is a tribe whose majority of the population used to be people who lived and settledin this region since the time of the formation of Batavia, they grew up and developed as a largeethnic group, the result of intermarriages and mixed marriages of various ethnic migrants.The form of acculturation can be seen in the designation of the clothes worn by the bride andgroom, namely the wedding dress 'haji care' for the bride and groom, and the "rias besar dandanancare none pengantin cine" for the bride. In this study will reveal a lot of the elements of formand symbolic meaning embedded in it, then the method in this research is descriptive analysiswith qualitative methods, the analysis process uses visual art review theory, descriptive in nature,where data and pictures will be broken down and explanations about various things relating tothe visual elements in the object of research that have been redrawn with illustration techniques.The most interesting finding in this study is the existence of different absorption elements, inthis Betawi bridal costume is in the bride costume thick with Chinese culture, but in the malecostume, thick with nuances of Arabic culture, and as we know that in history two this culturereally has a strong influence on the development and growth of Betawi people.